Persecutory ideation and anomalous perceptual experiences in the context of the COVID-19 outbreak in France: what's left one month later?. (February 2021) - Bortolon, Catherine; Capdevielle, Delphine; Dubreucq, Julien; Raffard, Stéphane
Abstract: Purpose: Beyond the effects of the coronavirus pandemic on the public's health, the length of lockdown and its possible psychological impacts on populations is heavily debated. However, the consequences of lockdown on psychotic symptoms have been poorly investigated. Methods: An online survey was run from April 13 to May 11, 2020; a total of 728 French subjects from the general population were included in the study. We assessed the perceived impact of the COVID-19 outbreak, length of isolation, diagnosis/symptoms/hospitalisation related to the COVID-19 (oneself and family). Paranoid ideations and hallucination-like experiences were assessed via the Paranoia Scale and the Cardiff Anomalous Perceptions Scale, respectively. Self-reported measures of negative affect, loneliness, sleep difficulties, jumping to conclusion bias, repetitive thoughts, among others, were also included. Results: Final regression model for paranoia indicated that socio-demographic variables (age, sex and education), loneliness, cognitive bias, anxiety, experiential avoidance, repetitive thoughts and hallucinations were associated with paranoia (R 2  = 0.43). For hallucinations, clinical variables as well as the quality of sleep, behavioural activation, repetitive thoughts, anxiety and paranoia were associated with hallucinations in our sample (R 2  = 0.27). Neither length of isolation nor the perceived impact of the COVID-19 pandemic were associated with psychotic experiences in the final models. Conclusions: No evidence was found for the impact of isolation on psychotic symptoms in the general population in France one month after the lockdown. It nevertheless confirms the preeminent role of several factors previously described in the maintenance and development of psychotic symptoms in the context of a pandemic and lockdown measures. Highlights: Paranoia and Hallucinations levels in general population were relatively low. Paranoia was not statistically significant associated with COVID-19 related variables. Hallucination was not statistically significant associated with COVID-19 related variables. Paranoia was associated mainly with cognitive-affective variables. Hallucinations were associated with clinical variables, quality of sleep, affect and paranoia.